PENERIMAAN CELAH YANG DITERIMA DAN EFEKTIFITAS ZEBRA CROSS PADA JALAN PROF. A. MAJID IBRAHIM, KOTA SIGLI - Saiful Saiful; Sugiarto Sugiarto; Renni Anggraini (Prodi Magister Teknik Sipil Unsyiah, 2018)
Along with urbanism and rapid motorization in the Pidie district leads to increasing private-mode dependency. Increasing number of the vehicle used in urban road networks could affect the pedestrian crossing facilities, especially within the school zone. Therefore, this study aims to evaluate the needs for pedestrian crossing facilities within school zone located at Prof. A. Majid Ibrahim Road in the Pidie District. The gap acceptance approach is used to evaluate accepted and rejected gaps. Furthermore, the effectiveness of the pedestrian crossing (Zebra Cross) regarding whether it is truly appropriate or not then evaluates using the statistical method of hypothesis testing. The analysis result reveals that the higher speed in the traffic, the greater gap required by crosser. The average speed for the traffic direction of Medan - Banda Aceh is about 47,13 km/h; pedestrians require the distribution of gap value of 85% or about 7 m crossing distance is necessary to available. At the location of the zebra cross 1, in the morning and noon observations show the average gap is about 7.71 and 9.18 seconds, respectively. Furthermore, as for the location of the zebra cross 2, in the morning and noon observations show the average gap is about 8.69 and 10.20 seconds, respectively. Based on the gap distribution, it concluded that the zebra cross facility at Prof. A. Majid Ibrahim Road is still worth using. As for the effectiveness of zebra cross, based on 85% speed at a distance from 50 m and 30 m can be concluded that zebra cross at Prof. A. Majid Ibrahim Road is ineffective. The absence of a decreasing in vehicle speed as it passes through the zebra cross, the velocity of the vehicle at 50 m from the zebra cross ≥ 30 m from the zebra cross. The speed of the vehicle tends to be stable at the time of going through the zebra cross.